Using Technology in the Library Workplace : An Introduction for Support Staff - Shaw, Marie Keen, author 643515 (Lanham : Rowman & Littlefield, 2021)
"This text is written for the library support staff who are the backbone of technology success. Each chapter provides a practical overview of how the technology advances library services. With abundant examples of how to apply the technology in real situations, it is an essential handbook for students entering into the library profession"--